2016
DOI: 10.1002/rrq.134
|View full text |Cite
|
Sign up to set email alerts
|

Factorial and Construct Validity of a New Instrument for the Assessment of Reading Motivation

Abstract: A B S T R A C TReading motivation has been defined consistently as a multidimensional construct. However, there is some disagreement regarding the number and nature of the dimensions of reading motivation. In particular, there is a lack of studies investigating the dimensional structure and measurement invariance (e.g., across gender) of reading motivation questionnaires. Based on earlier instruments, qualitative findings referring to students' reasons for reading, and theoretical considerations, we developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 65 publications
4
68
1
2
Order By: Relevance
“…This is a problem that related studies also had to deal with (cf. Miesen, ; Schiefele & Schaffner, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a problem that related studies also had to deal with (cf. Miesen, ; Schiefele & Schaffner, ).…”
Section: Discussionmentioning
confidence: 99%
“…Taking a closer look at the existing questionnaires on determinants of student reading including the MRQ (Möller & Bonerad, ; Schaffner & Schiefele, ; Schiefele & Schaffner, ; Wigfield & Guthrie, , ), it becomes obvious that they tend to stress the importance of intrapersonal aspects while paying less attention to the subjective evaluation of environmental circumstances, such as the availability of books, the availability of time, or cost–benefit considerations. However, research on various leisure time activities has shown that such environmental factors also affect the conscious decision on whether to engage in a behavior or to avoid it (e.g., Murnaghan et al., ; Rhodes & Dean, ; van Schooten, de Glopper, & Stoel, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Contacting those people from different areas provided rich amount of feedbacks for finalizing the measure. The fourth stage was exploratory factor analysis which reveals factor structure of the scales and provides evidence for construct validity (Museus, Zhang & Kim, 2016;Schiefele & Schaffner, 2016). Each item was responded on a 9-point rating scale ranging from "very poorly" to "very well" in order to avoid difficulty in differentiating responses (Uzuntiryaki & Aydın, 2009).…”
Section: Instrumentationmentioning
confidence: 99%
“…Reading motivation has often been proven to be a multidimensional construct (Wigfield & Guthrie, 1997;Schiefele & Schaffner, 2016). This includes activityrelated reading motivation (the readiness to read) and object-related reading motivation (interest in specific texts and in the contents of texts).…”
Section: Introductionmentioning
confidence: 99%